A meta‐analysis comparing standard polyethylene and oxygen barrier film in terms of losses during storage and aerobic stability of silage. (9th October 2013) - Wilkinson, J. M.; Fenlon, J. S.
Abstract A meta‐analysis was undertaken of 51 comparisons of standard polyethylene film with oxygen barrier (OB) film in covering systems for bunker silos, unwalled clamp silos and bales. Mean losses of DM or OM during storage from the top 10 to 60 cm of bunker and clamp silos were 195 g kg−1 for standard film and 114 g kg−1 for OB film systems (41 sets of data, P < 0·001), while mean total losses of DM from baled silage were 76·8 g kg−1 for standard film and 45·6 g kg−1 for OB film systems (10 sets of data, P < 0·001). Top surface silage judged subjectively to be inedible was 107 and 29·6 g kg−1 for standard film and OB film systems respectively (5 sets of data, P = 0·02). Aerobic stability was 75 h for silage stored under standard film system and 135 h for silage stored under OB film system (11 sets of data, P = 0·001). It is concluded that the OB film system reduces losses from the outer layers of silos and from bales and increases the aerobic stability of silage in the outer layers of silos.